Stock Market Response to Unexpected Macroeconomic News : The Australian Evidence - Sadeghi, Mahdi (IMF Working Papers; Working Paper ;, 1992)
This paper provides empirical evidence on the relationship between unexpected changes in macroeconomic variables and Australian stock returns over the period 1980-1991. The results suggest that stock returns are positively correlated with any surprise news in the current account deficit, the exchange rate and growth rate of real GDP, and negatively correlated with surprise news about the inflation rate and interest rates. Stock returns are also positively correlated with the unexpected unemployment rate and negatively correlated to revisions in the expected unemployment rate. The results furthermore suggest that market portfolios can detect the impact of common economic shocks better than the portfolios of the two main subsectors of the market.